Assessing the Relationship Between Motor Anticipation and Cortical Excitability in Subacute Stroke Patients With Movement-Related Potentials - Chen, Ling; Mao, Yurong; Ding, Minghui; Li, Le; Leng, Yan; Zhao, Jiangli; Xu, Zhiqin; Huang, Dong Feng; Lo, Wai Leung Ambrose (Frontiers in Neurology, 2018)
Background: Stroke survivors may lack the cognitive ability to anticipate the required control for palmar grasp execution. The cortical mechanisms involved in motor anticipation of palmar grasp movement and its association with post-stroke hand function remains unknown. Aims: To investigate the cognitive anticipation process during a palmar grasp task in subacute stroke survivors and to compared with healthy individuals. The association between cortical excitability and hand function was also explored. Methods: Twenty-five participants with hemiparesis within 1 to 6 months after first unilateral stroke were recruited. Twenty-five matched healthy individuals were recruited as control. Contingent negative variation (CNV) was measured using electroencephalography recordings (EEG). Event related potentials were elicited by cue triggered hand movement paradigm. CNV onset time and amplitude between pre-cue and before movement execution were recorded. Results: The differences in CNV onset time and peak amplitude were statistically significant between the subacute stroke and control groups, with patients showing earlier onset time with increased amplitudes. However, there was no statistically significant difference in CNV onset time and peak amplitude between lesioned and non-lesioned hemisphere in the subacute stroke group. Low to moderate linear associations were observed between cortical excitability and hand function. Conclusions: The earlier CNV onset time and higher peak amplitude observed in the subacute stroke group are increased brain computational demand during palmar grasp task. The lack of difference in CNV amplitude between the lesioned and non-lesioned hemisphere within the subacute stroke group may suggest that the non-lesioned hemisphere plays a role in the motor anticipatory process. The moderate correlations suggested that hand function may be associated with cortical processing of motor anticipation.